Defect inspection for house construction / Nurul Fatin Idayu Azman - Azman, Nurul Fatin Idayu (Universiti Teknologi MARA UiTM,Perak, 2022)
This chapter will briefly describe the objective and duration of industrial training at NH Ivory Home Sdn. Bhd. It also will state the scope of work and functions of the company. It also will explain the detail of the company background, vision, mission, and objective of the company. This chapter will provide some other information related to the company such as the location of the office, company organization chart, scope of work, and their responsibilities. The method that will be used to collect all the information is by an interview with some staff and through the information board.